2009
DOI: 10.1021/es8031852
|View full text |Cite
|
Sign up to set email alerts
|

Two-Decade Reconstruction of Algal Blooms in China’s Lake Taihu

Abstract: The algal blooming in the inland lakes has become a critically important issue for its impacts not only on local natural and social environments, but also on global human community. However, the occurrences of blooming on larger spatial scale and longer time scale have rarely been studied. As the third largest freshwater lake in China, Lake Taihu has drawn increasing attention from both public and scientific communities concerning its degradation. Using available satellite images, we reconstructed the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
273
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(282 citation statements)
references
References 37 publications
7
273
0
2
Order By: Relevance
“…Two groups from Taihu Lake (ThS and ThW) had mean ses.betaMNTD values that were less than zero (Supplementary Figure S3), suggesting that for both groups there was relative consistency in the environmental conditions that deterministically governed community composition. Although many features of the observed abiotic environment in Taihu Lake varied across sampled communities, a high level of eutrophication was maintained across communities (Duan et al, 2009). It may therefore be that high eutrophication imposed strong environmental filtering on microbial communities in Taihu Lake.…”
Section: Phylogenetic Signal Varies With Phylogenetic Distancementioning
confidence: 95%
“…Two groups from Taihu Lake (ThS and ThW) had mean ses.betaMNTD values that were less than zero (Supplementary Figure S3), suggesting that for both groups there was relative consistency in the environmental conditions that deterministically governed community composition. Although many features of the observed abiotic environment in Taihu Lake varied across sampled communities, a high level of eutrophication was maintained across communities (Duan et al, 2009). It may therefore be that high eutrophication imposed strong environmental filtering on microbial communities in Taihu Lake.…”
Section: Phylogenetic Signal Varies With Phylogenetic Distancementioning
confidence: 95%
“…West (n = 16) South (n = 24) (Song et al, 2007;Duan et al, 2009;Ye et al, 2009). It is assumed that water from Lake Taihu might present a risk of heavy metal transfer from the lake into crops grown using the water from the lake for irrigation.…”
Section: North (N = 24)mentioning
confidence: 99%
“…A large number of studies have indicated that Lake Taihu is profoundly affected by cyanobacterial blooms, and control strategies such as reducing nutrient by sediment dredging and chemical methods, and phytoremedation have been implemented in the last few years (Duan et al, 2009;Paerl et al, 2011;Zhang et al, 2016;Tang et al, 2016;Xu et al, 2017). In our previous study, we focused on the investigation how mechanical collection of cyanobacterial biomass was degraded in the artificial ponds and the risk associated with this process (Chen et al, 2012).…”
Section: Risks Of Heavy Metals Transfer From Waterbody To Vegetablesmentioning
confidence: 99%
“…5). There are considerable evidences (surface water chemistry, sediment cores, and satellite imagery) indicating that these three lakes are experiencing significant increases in algal productivity both over time and space (Duan et al 2009;Shang and Shang 2007;Zhu 2008). From 1987 to 2007, algal blooms in Taihu Lake occurred at increasing frequency and on lengthened duration while the distribution area became larger and larger year by year (Duan et al 2009).…”
Section: Eutrophication Control In China: Are We Well Prepared?mentioning
confidence: 99%
“…There are considerable evidences (surface water chemistry, sediment cores, and satellite imagery) indicating that these three lakes are experiencing significant increases in algal productivity both over time and space (Duan et al 2009;Shang and Shang 2007;Zhu 2008). From 1987 to 2007, algal blooms in Taihu Lake occurred at increasing frequency and on lengthened duration while the distribution area became larger and larger year by year (Duan et al 2009). The average TSI (Trophic State Index) of western Chaohu Lake increased slightly from 72.6 between 1984 and 1991 to 75.4 between 1998 and 2004 in spite of the fact that during last two decades a series of measures have been taken by national and local government to restrain the eutrophication process in the lake (Shang and Shang 2007).…”
Section: Eutrophication Control In China: Are We Well Prepared?mentioning
confidence: 99%